2019
DOI: 10.1029/2019gl083148
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Wedge Failure and Along‐Arc Variations of Tsunamigenesis in the Japan Trench Margin

Abstract: Elastic dislocation models require large near‐trench slip to explain large tsunamigenesis, which is probably best exemplified in the 2011 M9 Tohoku earthquake. However, it is puzzling that the largest Tohoku tsunami heights occurred about 100 km north of the largest slip zone, where bathymetric surveys indicate no large slip at the trench or submarine landslides. Here we show that coseismic yielding of plentiful sediments in the northern Japan Trench margin can induce large inelastic uplift landward from the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
57
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 61 publications
4
57
0
Order By: Relevance
“…However, this does not mean that erosional margins are completely devoid of sediment cover (Clift and Vannucchi, 2004). It has been suggested that the presence of sediments could enhance tsunamigenesis, by promoting larger uplift (Ma and Nie, 2019). This could explain the large range of N t for subduction zone segments with moderate sediment cover (i.e., T sed ≤ 2 km; Fig.…”
Section: Which Tectonic Setting Is More Prone To Host Tsunamigenic Eamentioning
confidence: 98%
“…However, this does not mean that erosional margins are completely devoid of sediment cover (Clift and Vannucchi, 2004). It has been suggested that the presence of sediments could enhance tsunamigenesis, by promoting larger uplift (Ma and Nie, 2019). This could explain the large range of N t for subduction zone segments with moderate sediment cover (i.e., T sed ≤ 2 km; Fig.…”
Section: Which Tectonic Setting Is More Prone To Host Tsunamigenic Eamentioning
confidence: 98%
“…Computational earthquake models that are able to account for the curved thrust interface and splay fault networks intersecting with bathymetry, the narrow accretionary wedge, and the complex lithology of subduction zones are challenging. Off-fault yielding processes, which can significantly modulate fault slip near the trench (e.g., (45,81)), pose additional computational demands. These challenges are addressed using the SeisSol software package (e.g., (82)(83)(84)), which solves the nonlinear coupled problem of spontaneous frictional failure across prescribed fault surfaces, seismic wave propagation, and (visco-)plastic Drucker-Prager off-fault damage (e.g., (42)).…”
Section: Earthquake Computational Modelmentioning
confidence: 99%
“…We then analyze a major conundrum (45) of earthquake-tsunami interaction that is ill-constrained by observational data: the interplay of near-trench earthquake dynamics and sedimentary yielding controlling tsunami generation and propagation. We present two additional scenarios with alternative near-trench sedimentary rock strength.…”
mentioning
confidence: 99%
See 2 more Smart Citations